(untitled) (DAPesquisa, 2020)
The study explores the solidarity economy in the textile and fashion area. The objective is the bibliographic survey and data analysis to understand how this economy emerged and developed in the world and in Brazil, for the proper deepening in the area of textile confection. The method included bibliographic research conducted through library catalogs and journals portal of the Coordination of Improvement of Higher Level Personnel and Integrated Library System of the University of São Paulo, as well as systematic review of postgraduate articles. already produced. The gathering of this information offered subsidies to address two examples of solidary economic groups in fashion and their eventual difficulties to act in the capitalist market. It was possible to detect the importance of cooperativism, marked by its successful experiences. For the absorption of people who cannot find a place in the capitalist economy to occur, the support of the labor movement to the workers’ cooperatives is necessary. Thus, it becomes necessary to think about how egalitarian communities and enterprises can live with the dominant capitalist model.